DNA methylation regulates B cell activation via repressing Pax5 expression in teleost - Shi, Yuan; Zhu, Zhuo; Chen, Qiuxuan; Chen, Xinhua (Frontiers in Immunology, 2024)
In mammals, the transcription factor Pax5 is a key regulator of B cell development and maturation and specifically expressed in naive/mature B cells but repressed upon B cell activation. Despite the long-standing proposal that Pax5 repression is essential for proper B cell activation, the underlying mechanisms remain largely elusive. In this study, we used a teleost model to elucidate the mechanisms governing Pax5 repression during B cell activation. Treatment with lipopolysaccharide (LPS) and chitosan oligosaccharide (COS) significantly enhanced the antibody secreting ability and phagocytic capacity of IgM + B cells in large yellow croaker (Larimichthys crocea), coinciding with upregulated expression of activation-related genes, such as Bcl6, Blimp1, and sIgM, and downregulated expression of Pax5. Intriguingly, two CpG islands were identified within the promoter region of Pax5. Both CpG islands exhibited hypomethylation in naive/mature B cells, while CpG island1 was specifically transited into hypermethylation upon B cell activation. Furthermore, treatment with DNA methylation inhibitor 5-aza-2'-deoxycytidine (AZA) prevented the hypermethylation of CpG island1, and concomitantly impaired the downregulation of Pax5 and activation of B cells. Finally, through in vitro methylation experiments, we demonstrated that DNA methylation exerts an inhibitory effect on promoter activities of Pax5. Taken together, our findings unveil a novel mechanism underlying Pax5 repression during B cell activation, thus promoting the understanding of B cell activation process.